Burrow - Spilsbury, Richard (Chicago : Heinemann Library, 2013)
Look inside a burrow and discover a world of inhabitants! A close look at this microhabitat reveals an unbelievable variety of organisms. Vibrant photographs and detailed illustrations combine to make these books informative and engaging. A visual table of contents helps readers navigate the text, and informative labels make the photographs valuable sources of information.
Above the burrow -- Shallow burrows -- Inside the burrow -- Deep burrows -- Burrow habitats.
Keywords: Burrowing animals; Burrower bugs; Niche (Ecology); Burrowing animals; Burrower bugs; Niche (Ecology)